2018
DOI: 10.7554/elife.36398
|View full text |Cite
|
Sign up to set email alerts
|

Host genetic selection for cold tolerance shapes microbiome composition and modulates its response to temperature

Abstract: The hologenome concept proposes that microbes and their host organism are an independent unit of selection. Motivated by this concept, we hypothesized that thermal acclimation in poikilothermic organisms, owing to their inability to maintain their body temperature, is connected to their microbiome composition. To test this hypothesis, we used a unique experimental setup with a transgenerational selective breeding scheme for cold tolerance in tropical tilapias. We tested the effects of the selection on the gut … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
105
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(110 citation statements)
references
References 59 publications
5
105
0
Order By: Relevance
“…Hibernation and estivation processes may help the species to cope with unfavorable temperatures (Bullard et al, 2007;Ordóñez et al, 2015). Our results indicate that temperature adaptation seems to be a driving force in the colonization process of D. vexillum, and the microbiome can play a role in the thermal adaptation of the species, as has been suggested in fish and corals (Kokou et al, 2018;Osman et al, 2020).…”
Section: Discussionsupporting
confidence: 68%
“…Hibernation and estivation processes may help the species to cope with unfavorable temperatures (Bullard et al, 2007;Ordóñez et al, 2015). Our results indicate that temperature adaptation seems to be a driving force in the colonization process of D. vexillum, and the microbiome can play a role in the thermal adaptation of the species, as has been suggested in fish and corals (Kokou et al, 2018;Osman et al, 2020).…”
Section: Discussionsupporting
confidence: 68%
“…Together these results indicate that the muscle-yield genetic lines are predictive of gut microbial assemblages and suggest that host genetic breeding might select for particular gut microbial assemblages. This notion is supported by recent studies in tilapia, showing host genetic selection effects for thermal tolerance on the microbiome composition [23]. Similarly, studies in stickleback fish identified association between gut microbial differences and host genetic divergence [24].…”
Section: Comparison Of Gut Assemblages In High-and Low-muscle Yield Gmentioning
confidence: 57%
“…Variations in microbiota composition within the same species can be due to many factors. Differences in environment [46,52], season [48], age [36,50,51], sex [36], diet [18,42] or genetic background [53] can di cult comparisons among studies. In addition, technical differences, such as part of the intestine sampled [52,81], type of sample (adherent, transient or total microbiota) [82,83], DNA extraction techniques or analysis methodology [84,85], can also be a source of variation.…”
Section: Discussionmentioning
confidence: 99%
“…These studies were mainly focused on de ning baseline populations [35][36][37] or changes induced by diet [18,[38][39][40][41][42][43][44] or environmental conditions [45]. The microbiota is composed of very dynamic populations that are affected by different factors [18,36,[53][54][55]42,[46][47][48][49][50][51][52] such as diet, season, habitat, rearing density, age, sex and genetic background, the focus of the current study. There are not many studies de ning the effects of the host genome on intestinal microbiota composition in sh.…”
Section: Introductionmentioning
confidence: 99%